De l’abstraction réelle de la monnaie au concret absolu du marché financier - Élie Ayache (Recherches Germaniques, 2020)
Marxist criticism considers the financial market as the utmost achievement of abstraction. It is the jewel of capitalism, which is in turn the accomplishment of metaphysics and of the Greek logos. This article argues, against this Marxist view, that the financial market should not be confused with capitalism, and even less so with the notions of algorithm and automatism. Indeed, it will show that once capitalism is augmented by the derivatives market, the financial market will no longer appear as an abstract structure, but rather as a concrete infrastructure, which presents an alternative to the foundation of the traditional schema of abstraction. It will effectively contradict abstract probability theory, which is founded on such a schema.